Russell and the foundations of qualitative spatial reasoning: the first steps. (2nd October 2021) - Trybus, Adam
ABSTRACT: We argue that the ideas of Bertrand Russell, a famous English philosopher and logician, have a bearing on the philosophical foundations of one of the sub–fields of AI, called qualitative spatial reasoning. The research conducted within that field focuses on non–numerical reasoning about regions of space designed to mimic human spatial behaviour and thus avoid the artificiality of the numerical approach. After briefly describing the main characteristics of this field, we analyse Russell's works on geometry. We show that despite major differences in how the subject matter is treated, these publications do have a common core that is related to the non–numerical, qualitative parts of geometry. Therefore, we argue that Russell should be viewed as a forefather of qualitative spatial reasoning on par with Whitehead or Leśniewski. Moreover, we believe that the efforts within qualitative spatial reasoning should be geared more towards the types of geometry he describes.